Dividend policy and investment: Theory and evidence from US panel data - Elston,Julie (Managerial and Decision Economics, 1996)
This paper examines the importance of dividend policy and liquidity constraints in the context of the firm's investment behaviour. While early financial literature has argued that dividend policy should be independent of firm investment decisions, recent studies indicate that linkages are probable in a world of imperfect capital markets. This study develops an alternative Q specification which incorporates the actual dividend payment of the firm in order to test the hypothesis of independence. Empirical results suggest that after controlling for the firm's dividend payment, liquidity constraints remain an important determinant of firm investment behavior.
Keywords: Finance; OSU-Cascades